SURGICAL TREATMENT OF MULTIPLE LUNG METASTASIS IN PATIENT WITH SOFT ISSUE AND VISCERAL SARCOMAS - E. I. Smolenov; Yu. A. Ragulin; A. L. Starodubtsev; A. A. Kuril’chik; V. E. Ivanov; A. L. Zubarev (Сибирский онкологический журнал, 2016)
Introduction. The aim of this study was to analyze the surgical treatment for multiple intrapulmonary metastases sarcomas of bone and soft tissue. Methods. This analysis includes retrospective survival data from 24 patients with soft tissue sarcomas and bone sarcomas who were treated from January 2004 to December 2014 in MRRC and meet the following criteria: the presence of more than four lesions in the lungs, no progression of the primary tumor, no distant metastases and overall satisfactory status (ECOG 0–1). Survival of patients assessed by Kaplan-Meier method. results. In total 49 pulmonary metastasectomy were performed. There were no postoperative deaths. In 4 patients underwent repeated operations. From this cohort 1-year survival has survived 10 patients (41.6 %), 5-year – 3 (12.5 %). 3 patients are alive 28, 62 and 139 months after surgery with no evidence of progression of tumors. conclusion. The detection of lesion in the pulmonary parenchyma is most often regarded as the poor prognosis of the disease. Individually tailored treatment strategy allows you to increase the overall life expectancy and improve quality of life. The surgical method can be considered as a stage of complex treatment, as in the progression of the disease in the lungs, and in synchronous lesions. Surgical repeated resection may be an appropriate treatment for patients with progression and the justified possibility of an operation.